Face preference in infancy and its relation to motor activity. (November 2014) - Libertus, Klaus; Needham, Amy
Infants' preference for faces was investigated in a cross-sectional sample of 75 children, aged 3 to 11 months, and 23 adults. A visual preference paradigm was used where pairs of faces and toys were presented side-by-side while eye gaze was recorded. In addition, motor activity was assessed via parent report and the relation between motor activity and face preference was examined. Face preference scores followed an inverted U-shaped developmental trajectory with no face preference in 3-month-olds, a strong face preference in 5- and 9-month-olds, and a weaker face preference in 11-month-olds. Adults showed no reliable face preference. Motor activity was a significant predictor of face preference in 3-month-old infants, supporting the presence of motor-social connections in early infancy.